Tuning bifunctional oxygen electrocatalysts by changing the A-Site rare-earth element in perovskite nickelates - Wang, Le (2020)
Perovskite-structured (ABO3) transition metal oxides are promising bifunctional electrocatalysts for efficient oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). In this paper, a set of epitaxial rare-earth nickelates (RNiO3) thin films is investigated with controlled A-site isovalent substitution to correlate their structure and physical properties with ORR/OER activities, examined by using a three-electrode system in O2-saturated 0.1 m KOH electrolyte. The ORR activity decreases monotonically with decreasing the A-site element ionic radius which lowers the conductivity of RNiO3 (R = La, La0.5Nd0.5, La0.2Nd0.8, Nd, Nd0.5Sm0.5, Sm, and Gd) films, with LaNiO3 being the most conductive and active. On the other hand, the OER activity initially increases upon substituting La with Nd and is maximal at La0.2Nd0.8NiO3. Moreover, the OER activity remains comparable within error through Sm-doped NdNiO3. Beyond that, the activity cannot be measured due to the potential voltage drop across the film. The improved OER activity is ascribed to the partial reduction of Ni3+ to Ni2+ as a result of oxygen vacancies, which increases the average occupancy of the eg antibonding orbital to more than one. The work highlights the importance of tuning A-site elements as an effective strategy for balancing ORR and OER activities of bifunctional electrocatalysts.